2013
DOI: 10.1096/fj.13-240556
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding‐dependent functions of the lipocalin NLaz: anin vivostudy inDrosophila

Abstract: Lipocalins are small extracellular proteins mostly described as lipid carriers. The Drosophila lipocalin NLaz (neural Lazarillo) modulates the IIS pathway and regulates longevity, stress resistance, and behavior. Here, we test whether a native hydrophobic pocket structure is required for NLaz to perform its functions. We use a point mutation altering the binding pocket (NLaz(L130R)) and control mutations outside NLaz binding pocket. Tryptophan fluorescence titration reveals that NLaz(L130R) loses its ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 67 publications
1
26
0
2
Order By: Relevance
“…A type of lipocalin was validated here in the integument of intermediate pharate adults (Pbl phase) at the onset of cuticle pigmentation and may be related to the transport of products for cuticle differentiation. A recent work using a point mutation to alter the ligand binding capacity of a Drosophila lipocalin suggested that this protein binds to ergosterol (the functional equivalent to mammalian cholesterol in insects) and to the pheromone 7(z)‐tricosene, indicating a specific function of lipocalin as a mediator of pheromone signals (Ruiz et al., ). Like the lipocalin here validated, the 7(z)‐tricosene hydrocarbon was identified in the cuticular envelope of A. mellifera pharate adults (Falcón et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A type of lipocalin was validated here in the integument of intermediate pharate adults (Pbl phase) at the onset of cuticle pigmentation and may be related to the transport of products for cuticle differentiation. A recent work using a point mutation to alter the ligand binding capacity of a Drosophila lipocalin suggested that this protein binds to ergosterol (the functional equivalent to mammalian cholesterol in insects) and to the pheromone 7(z)‐tricosene, indicating a specific function of lipocalin as a mediator of pheromone signals (Ruiz et al., ). Like the lipocalin here validated, the 7(z)‐tricosene hydrocarbon was identified in the cuticular envelope of A. mellifera pharate adults (Falcón et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression levels of invertebrate ApoD homologues have been shown to modulate longevity (Hull-Thompson et al, 2009;Ruiz et al, 2011Ruiz et al, , 2012Ruiz et al, , 2014Sanchez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For co-cultures, cells were counted with Countess Automated Cell Counter (Invitrogen). For the exogenous addition of ApoD, human ApoD purified from breast cystic fluid [18] or recombinant human ApoD from E. coli (ProSpec) were added (10 nM) to the cell cultures for 2 h. For long-term treatment (7 days), media was replaced every 48-72 h with freshly added ApoD. The expression constructs used in this work (pcDNA3.1-ApoD; pHSVer-GA;…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…These methods were performed as previously described [18,34] The fluorescence spectrum in the presence of ligand was subtracted from DMF baseline obtained mixing the protein with the same amounts of carrier without ligand.…”
Section: Ligand Binding Assay By Tryptophan Fluorescence Titrationmentioning
confidence: 99%
See 1 more Smart Citation